CERPEN “REMBULAN DI DASAR KOLAM” KARYA DANARTO DALAM HERMENEUTIK PAUL RICOEUR - Yulia Nasrul Latifi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
Danarto’s Rembulan di Dasar Kolam (The Moon Beneath the Pond) tells about a wife’s sacrifice in an unfortunate situation. The wife, is an unfortunate woman whose husband cheats and treats her disrespectfully. Yet, her spirituality endures her in such situation. Paul Ricoeur’s hermeneutics theory proposes the hypothesis that the analysis of symbol is a guide to the analysis of text, and the other way around. Both must be submitted to a process of metamorphosis or dialectical phenomena. The result of this analysis is the emergence of symbolical meaning in various terms. Rabi’ah becomes a symbol of a wife’s strength. Her wisdom and personality give the way out to her household problems. Her social status as well as gender role is the symbol that religiosity belongs to anyone despite one’s social status. From this character, it can be seen that the knowledge of spiritualism is aimed not only vertically (to God) but also horizontally (to humanity). The title Rembulan or the Moon symbolizes the wife, because, despite her condition- symbolized as the pond-she endures and still gives her shine, like the moon.